Dean Acheson with Fletcher Dean Robert Stewart and two female students - Unknown (Tufts Archival Research Center, 2007)
8x10; left to right: Dean Acheson, Noreen Glover, Fletcher Dean Robert Stewart and Mary Assimacopoulou